TICCAD used by university teachers in the post-pandemic: student perspective - Angélica Crespo Cabuto; Sonia Verónica Mortis Lozoya; Elizabeth del Hierro Parra (Universidad de Guadalajara, 2024)
The objective of the research was to identify the perspectives of university students on the use of information, communication and knowledge and digital learning technologies (TICCAD) in the post-pandemic by teachers. It is a qualitative study with a phenomenological approach, 41 students from two universities participated in four focus groups through a semi-structured interview with eight questions. The results showed that the main TICCAD used by teachers to identify prior knowledge, process information, develop integrative projects, work collaboratively, undertake, reflect on achievements and provide feedback are: Canva, Google Drive, Kahoot!, Moodle and Google Docs. In addition, students recommend that teachers receive training and an open attitude towards the use of new tools. As limitations, the importance of conducting a greater number of focus groups with students from related careers, to obtain more information, was highlighted. Furthermore, due to the few studies on the topic in the post-pandemic, the research is an important contribution to the integration of ICTCAD in educational processes. It is concluded that technological tools are valuable support in the teaching-learning process, since they facilitate access to information, exploration and discovery of knowledge, to enrich the educational experience.